Mouse Astrocytes Promote Microglial Ramification by Releasing TGF-β and Forming Glial Fibers - Zhang, Jinqiang (Front Cell Neurosci, 2020)
The morphology of microglial cells is often closely related to their functions. The mechanisms that regulate microglial ramification are not well understood. Here we reveal the biological mechanisms by which astrocytes regulate microglial ramification. Morphological variation in mouse microglial cultures was measured in terms of cell area as well as branch number and length. Effects on microglial ramification were analyzed after microinjecting the toxin L-alpha-aminoadipic acid (L-AAA) in the mouse cortex or hippocampus to ablate astrocytes, and after culturing microglia on their own in an astrocyte-conditioned medium (ACM) or together with astrocytes in coculture. TGF-β expression was determined by Western blotting, immunohistochemistry, and ELISA. The TGF-β signaling pathway was blocked by the TGF-β antibody to assess the role of TGF-β on microglial ramification. The results showed that microglia had more and longer branches and smaller cell bodies in brain areas where astrocytes were abundant. In the mouse cortex and hippocampus, ablation of astrocytes by L-AAA decreased number and length of microglial branches and increased the size of cell bodies. Similar results were obtained with isolated microglia in culture. However, isolated microglia were able to maintain their multibranched structure for a long time when cultured on astrocyte monolayers. Ameboid microglia isolated from P0 to P3 mice showed increased ramification when cultured in ACM or on astrocyte monolayers. Microglia cultured on astrocyte monolayers showed more complex branching structures than those cultured in ACM. Blocking astrocyte-derived TGF-β decreased microglial ramification. Astrocytes induced the formation of protuberances on branches of microglia by forming glial fibers that increased traction. These experiments in mice suggest that astrocytes promote microglial ramification by forming glial fibers to create traction and by secreting soluble factors into the surroundings. For example, astrocyte-secreted TGF-β promotes microglia to generate primitive branches, whose ramification is refined by glial fibers.